Regulatory T cells are expanded by Teriparatide treatment in humans and mediate intermittent PTH‐induced bone anabolism in mice. (20th November 2017) - Yu, Mingcan; D'Amelio, Patrizia; Tyagi, Abdul Malik; Vaccaro, Chiara; Li, Jau‐Yi; Hsu, Emory; Buondonno, Ilaria; Sassi, Francesca; Adams, Jonathan; Weitzmann, M Neale; DiPaolo, Richard; Pacifici, Roberto
Abstract: Teriparatide is a bone anabolic treatment for osteoporosis, modeled in animals by intermittent PTH (iPTH) administration, but the cellular and molecular mechanisms of action of iPTH are largely unknown. Here, we show that Teriparatide and iPTH cause a two‐threefold increase in the number of regulatory T cells (Tregs) in humans and mice. Attesting in vivo relevance, blockade of the Treg increase in mice prevents the increase in bone formation and trabecular bone volume and structure induced by iPTH. Therefore, increasing the number of Tregs is a pivotal mechanism by which iPTH exerts its bone anabolic activity. Increasing Tregs pharmacologically may represent a novel bone anabolic therapy, while iPTH‐induced Treg increase may find applications in inflammatory conditions and transplant medicine. Synopsis: Parathyroid hormone (PTH) causes a two–threefold increase in the number of regulatory T cells (Tregs) in humans and mice, an effect which is required for PTH to exert its bone anabolic activity. Parathyroid hormone (PTH) increases the number of regulatory T cells (Tregs) in humans and mice. Blockade of the PTH‐induced increase in Tregs prevents iPTH‐induced bone anabolism. Abstract : Parathyroid hormone (PTH) causes a two–threefold increase in the number of regulatory T cells (Tregs) in humans and mice, an effect which is required for PTH to exert its bone anabolic activity.